Examining How Biology Teachers' Pedagogical Beliefs Shape the Implementation of the Omani Reform-Oriented Curriculum - Intisar Ambusaidi; Bernard Badiali; Khalid Alkharousi (Athens Institute for Education and Research, 2021)
Research on science-education reform affirms the importance of taking into consideration teachers' pedagogical beliefs in relation of the constructivist perspective to ensure successful implementation of a reform-oriented curriculum. In addition, prominent studies pinpoint the need for teachers to have sufficient pedagogical content knowledge (PCK) to adapt a reform-oriented science curriculum to meet students' abilities and interests. This study focused on the reform-oriented science curriculum in Oman, and in particular, the grade 12 biology curriculum. The new biology curriculum emphasizes constructivism and encourages student-centered instruction, inquiry-based learning, cooperative learning, problem-solving, and critical thinking. However, since its implementation in 2008, various obstacles and challenges have been reported by teachers. These include a mismatch between the planned curriculum and the implemented curriculum. This mismatch has been attributed to a lack of motivation and PCK among teachers that would allow them to shift their teaching practices. Consequently, the purpose of this study was to understand how teachers' pedagogical beliefs about student-centered learning have shaped their implementation of the curriculum. The study also sought to identify how biology teachers perceive the relationship between their PCK and their pedagogical decisions. An ethnographic approach to data analysis was employed, with multiple data sources including classroom observations, learning artifacts, reflections, and semi-structured interviews used. The findings of this ethnographic study indicate that Omani teachers' beliefs and PCK shape the implementation of the reform-oriented curriculum by influencing their conceptualization of the curriculum, their identification of students' misconceptions, their decisions about classroom teaching practices, and the level of their students' engagement. The results of this study corroborate and expand upon previous research that suggests that teachers' beliefs and PCK should be taken into consideration when designing and planning for new curriculum materials, teacher-education programs, and professional development opportunities.